Monster - Myers, Walter Dean 1937-; Myers, Christopher (New York, N.Y. HarperTempest, 1999)
While on trial as an accomplice to a murder, sixteen-year-old Steve Harmon records his experiences in prison and in the courtroom in the form of a film script as he tries to come to terms with the course his life has taken.
Michael L. Printz Award, 2000
Keywords: Trials (Murder) -- Fiction; Prisons -- Fiction; Self-perception -- Fiction; African Americans -- Fiction